In-Vitro cytotoxicity activity of Mallotus oppositifolius and Enantia polycarpa extracts against Human Foreskin Fibroblast (HFF) Cell Line - Ambe, Alain S.A.; Yapo, Cynthia Y.; Orsot, Bosson A.M.B.; Gnahoue, Goueh; Camara, Djeneb; Ouattara, Djakalia; Zirihi, Guede N. (European Scientific Journal, ESJ, 2016)
The use of plants in traditional medicine become very common nowadays throughout the world and in developing countries in particular. The current study was carried out aiming to evaluate the cytotoxicity of Mallotus oppositifolius (Geisel.) Müll.-Arg (Euphorbiaceae) and Enantia polycarpa (DC) Engl. and Diels (Annonaceae) two medicinal plants mostly used for human traditional medicine to treat diarrhea in Côte d’Ivoire on Human Foreskin Fibroblast (HFF) cells. These plants were selected after ethno-botanical investigations in southern Côte d’Ivoire. Therefore, The results proved that the ethanolic extract of Enantia polycarpa showed the biggest yield (56,4%). The 70 % éthanolic extract of Mallotus oppositifolius is not cytotoxic at 1000 µg / ml concentration, but mitogen. Our study has shown that the ethanolic extract of Mallotus oppositifolius stimulates HFF cells (131% of viability confluents cells and 156% of viability cells in division). While Enantia polycarpa seems cytotoxic on HFF cells at 1000 µg / ml concentration (36% of viability confluents cells and 55% of viability cells in division). The study revealed that the moderate use of these medicinal plants only represents a limited risk of toxicity.